Components of Collective Coping in Families Facing Chronic Illness - Wright, Amelia; O’Connell, Patrick (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore the core components of collective coping in families managing the challenges of chronic illness, focusing on how emotional, relational, and social processes interact to sustain resilience. Methods and Materials: A qualitative research design was employed using semi-structured interviews with 20 family members of patients living with chronic illness in Ireland. Participants were recruited through purposive sampling to ensure variation in roles, including spouses, parents, adult children, and siblings. Interviews were conducted either face-to-face or via secure online platforms, with each lasting between 60 and 90 minutes. Data collection continued until theoretical saturation was reached. Transcripts were analyzed thematically using NVivo software version 14, following an iterative coding process of open coding, categorization, and theme development. Reflexivity and peer debriefing were used to enhance credibility and trustworthiness. Findings: Four overarching themes emerged, each encompassing multiple subthemes. Emotional solidarity captured shared emotional expression, empathic support, hope maintenance, anxiety management, and the protection of vulnerable members. Collaborative problem-solving included shared decision-making, role and task distribution, resource pooling, adaptive planning, and conflict resolution. Meaning-making and resilience reflected reframing illness as a shared challenge, strengthening family identity, engaging in collective spiritual practices, and narrative sharing. External support and community connection encompassed reliance on social networks, healthcare partnerships, institutional support, peer networks, and advocacy. Collectively, these themes highlighted coping as a relational and communal process rather than an individual endeavor. Conclusion: The findings underscore that coping with chronic illness within families is fundamentally collective, rooted in shared appraisals, collaboration, and external resource integration. Recognizing these dynamics offers valuable insights for healthcare professionals and policy makers seeking to design family-centered interventions that enhance resilience and well-being.